Inhibition of proteasome rescues a pathogenic variant of respiratory chain assembly factor COA7. Issue 5 (18th March 2019) - Mohanraj, Karthik; Wasilewski, Michal; Benincá, Cristiane; Cysewski, Dominik; Poznanski, Jaroslaw; Sakowska, Paulina; Bugajska, Zaneta; Deckers, Markus; Dennerlein, Sven; Fernandez‐Vizarra, Erika; Rehling, Peter; Dadlez, Michal; et al.
Abstract: Nuclear and mitochondrial genome mutations lead to various mitochondrial diseases, many of which affect the mitochondrial respiratory chain. The proteome of the intermembrane space (IMS) of mitochondria consists of several important assembly factors that participate in the biogenesis of mitochondrial respiratory chain complexes. The present study comprehensively analyzed a recently identified IMS protein cytochrome c oxidase assembly factor 7 (COA7), or RESpiratory chain Assembly 1 (RESA1) factor that is associated with a rare form of mitochondrial leukoencephalopathy and complex IV deficiency. We found that COA7 requires the mitochondrial IMS import and assembly (MIA) pathway for efficient accumulation in the IMS. We also found that pathogenic mutant versions of COA7 are imported slower than the wild‐type protein, and mislocalized proteins are degraded in the cytosol by the proteasome. Interestingly, proteasome inhibition rescued both the mitochondrial localization of COA7 and complex IV activity in patient‐derived fibroblasts. We propose proteasome inhibition as a novel therapeutic approach for a broad range of mitochondrial pathologies associated with the decreased levels of mitochondrial proteins. Synopsis: Biogenesis of the mitochondrial protein COA7 reveals a novel approach for treating diseases associated with the decreased levels of mitochondrial proteins. Proteasome Inhibition of excessive cytosolic degradation of mitochondrial precursors has the potential to restore mitochondrial function. COA7 is synthesized in the cytosol and imported to the intermembrane space of mitochondria by the MIA pathway. COA7‐Y137C and COA7‐exon2Δ protein variants associated with mitochondrial encephalopathy are severely decreased in patient‐derived fibroblasts. Inefficient import of pathogenic COA7 proteins into mitochondria exposes them to an excessive degradation by the proteasome resulting in the impaired mitochondrial respiratory chain assembly. Proteasomal inhibition increases mitochondrial levels of COA7 and restores the function of the respiratory chain. Abstract : Biogenesis of the mitochondrial protein COA7 reveals a novel approach for treating diseases associated with the decreased levels of mitochondrial proteins. Proteasome Inhibition of excessive cytosolic degradation of mitochondrial precursors has the potential to restore mitochondrial function.